Industry 4.0 Developments towards the Fourth Industrial Revolution - Kumar, Kaushik; Zindani, Divya; Davim, J. Paulo (Manufacturing and Surface Engineering,, 2019)
This book provides an overview of the burgeoning next generation of industry- Industry 4.0, which promises to increase flexibility in manufacturing in tandem with mass communication, improved productivity and better quality. This volume provides a comprehensive and holistic overview of intelligent manufacturing, process planning, assessment of product development opportunities, aspects of risk management, education and qualification requirements, socio-technical considerations and the sustainability of business models. This volume will be of interest to engineers, entrepreneurs, academics and students working in these fields. .